2013
DOI: 10.1016/j.juro.2012.08.087
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Clinical Trial Comparing Plasmakinetic Resection of the Prostate with Holmium Laser Enucleation of the Prostate Based on a 2-Year Followup

Abstract: Plasmakinetic resection and holmium laser enucleation of the prostate are effective and safe treatments for benign prostatic hyperplasia. Holmium laser enucleation of the prostate can be applied to prostates of all sizes, and involves less risk of hemorrhage, decreased bladder irrigation and catheter times, as well as reduced hospital stay. Thus, we believe holmium laser enucleation of the prostate should be proposed as a potential new gold standard surgical therapy instead of transurethral resection of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 29 publications
5
74
2
1
Order By: Relevance
“…Several new therapeutic modalities have been reported as an alternative to monopolar TURP. [1][2][3][4][11][12][13][14][15] In a previous trial, the authors performed a meta-analysis of 20 randomized, controlled studies comparing transurethral electrovaporization and TURP for symptomatic prostate obstruction. 9 The authors concluded that electrovaporization techniques were as effective as monopolar TURP with decreased complication rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several new therapeutic modalities have been reported as an alternative to monopolar TURP. [1][2][3][4][11][12][13][14][15] In a previous trial, the authors performed a meta-analysis of 20 randomized, controlled studies comparing transurethral electrovaporization and TURP for symptomatic prostate obstruction. 9 The authors concluded that electrovaporization techniques were as effective as monopolar TURP with decreased complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Conventional transurethral resection of the prostate (TURP) still remains the gold standard for the surgical management of bladder outlet obstruction (BOO) caused by BPH, particularly in the patients with a prostate volume of <100 mL. 3,4 Nevertheless, significant complications remain associated with TURP and the general morbidity rate of TURP is 18% and the overall mortality rate ranges between 0.17% and 0.77%. 3,[5][6][7][8][9][10] Due to significant complication rates observed following TURP, several studies have evaluated the safety and efficacy of new surgical techniques to potentially minimize the risks of TURP to treat lower urinary tract symptoms (LUTS) resulting from BPH.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen RCTs with a total 2433 participants (mean age 67.53 years) finally met full inclusion criteria for current metaanalysis. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Figure 1 showed the flowchart of literature searches and Table 1 provided characteristics of the included trials. These studies were conducted in 7 different countries located in Europe, North America, and Asia.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%